2018
DOI: 10.1016/j.ajog.2018.07.016
|View full text |Cite
|
Sign up to set email alerts
|

SMFM Consult Series #46: Evaluation and management of polyhydramnios

Abstract: Polyhydramnios, or hydramnios, is an abnormal increase in the volume of amniotic fluid. Identification of polyhydramnios should prompt a search for an underlying etiology. Although most cases of mild polyhydramnios are idiopathic, the 2 most common pathologic causes are maternal diabetes mellitus and fetal anomalies, some of which are associated with genetic syndromes. Other causes of polyhydramnios include congenital infection and alloimmunization. The purpose of this document is to provide guidance on the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 43 publications
1
101
0
2
Order By: Relevance
“…Furthermore, studies have shown that the severity of polyhydramnios directly correlates with the risk of prenatal abnormality as well as antepartum complications, such as the increased risk for premature delivery. 4 Considering these findings, intramuscular corticosteroid administration is given in anticipation of a possible preterm delivery.…”
Section: Questions/discussion: Partmentioning
confidence: 99%
“…Furthermore, studies have shown that the severity of polyhydramnios directly correlates with the risk of prenatal abnormality as well as antepartum complications, such as the increased risk for premature delivery. 4 Considering these findings, intramuscular corticosteroid administration is given in anticipation of a possible preterm delivery.…”
Section: Questions/discussion: Partmentioning
confidence: 99%
“…Hydrops was defined as pleural effusion associated with either subcutaneous edema, ascites, or pericardial effusion [10]. Polyhydramnios was defined as increased amniotic fluid volume with a deepest vertical pocket above 8.0 cm or an amniotic fluid index above 24 cm, while moderate and severe polyhydramnios were defined as an amniotic fluid index above 30 and 35 cm, respectively [11]. Exclusion criteria were (a) preterm prelabor rupture of membranes (PPROMs), (b) chromosomal abnormalities, (c) other concomitant structural anomalies, and (d) placenta previa.…”
Section: Methodsmentioning
confidence: 99%
“…Indications for a detailed fetal anatomic examination include, but are not limited to, the following conditions: Previous fetus or child with a congenital, genetic, or chromosomal abnormality; Known or suspected fetal anomaly or known or suspected fetal growth restriction in the current pregnancy; Fetus at increased risk for a congenital anomaly, such as the following: Maternal pregestational diabetes or gestational diabetes diagnosed before 24 weeks’ gestation; Pregnancy conceived via assisted reproductive technology; Maternal body mass index of 30 kg/m 2 or higher; Multiple gestations; Abnormal maternal serum analytes; Teratogen exposure; First‐trimester nuchal translucency measurement of 3.0 mm or greater; Fetus at increased risk for a genetic or chromosomal abnormality, such as the following: Parental carrier of a chromosomal or genetic abnormality; Maternal age of 35 years or older at delivery; Positive screening test results for aneuploidy; Aneuploidy marker noted on an ultrasound examination; First‐trimester nuchal translucency measurement of 3.0 mm or greater; Other conditions affecting the fetus, including the following: Congenital infections; Maternal drug use; Alloimmunization; Oligohydramnios; Polyhydramnios; and Suspected placenta PAS or risk factors for PAS such as placenta previa in the third trimester or a placenta overlying a prior cesarean scar site …”
Section: Indicationsmentioning
confidence: 99%